The Realtionship Between Worm Infection and Clean and Healthy Living Behavior (PHBS) in Students of MI Nurul Falah Jatimulya Village, Sepatan Timur Subdistrict, 2024 - Saputra, Atang; Syafitri, Dini (Politeknik Kesehatan Kemenkes Jakarta II, 2024)
Worms are one of the infectious diseases that are susceptible to occur in school-age children in Indonesia. The highest prevalence of worms occurs in underprivileged population groups and poor environmental sanitation. Children aged 6-12 years are more susceptible to worm infections due to their high curiosity to play intensely with the ground. At that age, children still depend on their parents to maintain personal hygiene. The consequences of worm infections that occur in toddlers or school-age children can cause malnutrition so that children's growth and development are disrupted due to reduced protein and carbohydrate energy and can cause anemia. Worm infections will be reduced and can even be eliminated if efforts are made to live a clean and healthy life such as washing hands with soap, managing food properly, a clean environment and nutritious food. The specific objective is to reduce the prevalence of worms in school-age children in poorly sanitation areas of Indonesia, as well as improve children's health and quality of life through evidence-based interventions. The research was conducted by the purposive sampling method, fecal samples were examined by the sedimentation method using a centrifuge and the behavior of PHBS was assessed using a questionnaire and then analyzed with the Chi-Square statistical test. Results there was no significant association between hand washing behavior with soap, snack habits and rigid mat habits and the incidence of worms